INCIDENCE OF HYPOTENSION AND NAUSEA VOMITING IN SUBARACHNOID BLOCK ANESTHESIA TECHNIQUE IN CESAREAN SURGERY - Nandaswari, Ni Made Nilam; Parami, Pontisomaya; Suranadi, I Wayan; Senapathi, Tjokorda Gde Agung (E-Jurnal Medika Udayana, 2024)
Hypotension and nausea vomiting are common side effects in patients undergoing cesarean surgery with subarachnoid block anesthesia techniques. Cases of hypotension and nausea vomiting in this case are often found but research data in Indonesia, especially in Bali, is still very limited. Therefore, this research is important to do with the aim of knowing the incidence of hypotension and nausea vomiting in cesarean surgery with the subarachnoid block anesthesia technique at Prof. Dr. I.G.N.G Ngoerah General Hospital Denpasar.             This study used a prospective cross-sectional observational descriptive method. The study data were taken from the presence or absence of hypotension and nausea vomiting during and after cesarean surgery from April 2022 – June 2022. The data were analyzed using Microsoft Excel 2013 software to obtain characteristics of patient demographic data in the form of maternal age and gestational age, patient distribution based on height of sensory blockade, type and dose of antiemetics, type and dose of opioids, bleeding, incidence of hypotension, and incidence of nausea vomiting.             The results showed that the number of patients who experienced hypotension was 13 people (28.3%), and those who did not experience hypotension were 33 people (71.7%). A total of 30 people (65.2%) patients did not experience nausea vomiting, 8 people (17.4%) experienced nausea and 8 people (17.4%) experienced vomiting. By taking good precautions, it can reduce the side effects of hypotension and nausea vomiting.